Four drown among beer cans as boat-party of 15 capsizes
tag=1 data=Four drown among beer cans as boat-party of 15 capsizes tag=3 data=Canberra Times tag=8 data=ACCIDENTS%ALCOHOL tag=9 data=BATHURST ISLAND tag=32 data=TIPILOURA, STAN%COLLINS, BOB tag=34 data=PRSS tag=61 data=23 tag=62 data=Apr tag=63 data=1990